2023
DOI: 10.3390/microorganisms11122959
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID or Post-COVID-19 Condition: Past, Present and Future Research Directions

César Fernández-de-las-Peñas,
Arkiath Veettil Raveendran,
Rocco Giordano
et al.

Abstract: The presence of symptoms after an acute SARS-CoV-2 infection (long-COVID) has become a worldwide healthcare emergency but remains underestimated and undertreated due to a lack of recognition of the condition and knowledge of the underlying mechanisms. In fact, the prevalence of post-COVID symptoms ranges from 50% during the first months after the infection up to 20% two-years after. This perspective review aimed to map the existing literature on post-COVID symptoms and to identify gaps in the literature to gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 129 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Hence, vaccination should be prioritized over antivirals in high-risk patients, also from the cost-effective perspective, the risk of developing anti-viral resistance in case of widespread use of antivirals, as well as its potential effect on reduction of risk of post-COVID-19 sequelae. 22,23 This study revealed some interesting findings. First, the effectiveness of nirmatrelvir-ritonavir was not ideal in patients with mild-to-moderate liver dysfunction.…”
mentioning
confidence: 63%
“…Hence, vaccination should be prioritized over antivirals in high-risk patients, also from the cost-effective perspective, the risk of developing anti-viral resistance in case of widespread use of antivirals, as well as its potential effect on reduction of risk of post-COVID-19 sequelae. 22,23 This study revealed some interesting findings. First, the effectiveness of nirmatrelvir-ritonavir was not ideal in patients with mild-to-moderate liver dysfunction.…”
mentioning
confidence: 63%
“…The underlying mechanisms explaining the development of post-COVID symptoms are not fully understood, and different mechanisms are proposed: viral persistence, long-lasting inflammation, immune system dysregulation, autoimmunity, the reactivation of latent infections, endothelial dysfunction, and alteration in the gut microbiota [ 32 ]. Our study did not find an association between the four SNPs associated with inflammation and the development of post-COVID symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID, also called PASC, presents as a complex and multifaceted illness affecting a significant proportion of individuals recovering from an acute COVID-19 infection [17]. Among the most common symptoms of long COVID are chronic fatigue, fever, pain, breathlessness, anxiety, chronic fatigue syndrome, and postural orthostatic tachycardia syndrome (POTS) [13,17]. Additional general symptoms may include fatigue, fever, and pain [18].…”
Section: Overview Of Symptomsmentioning
confidence: 99%